An evaluation of heatmount detectors in beef cattle under range conditions - A.R. Singh; G.H. Kiracofe; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1969)
Kamar heatmount detectors were used last spring on 45 Polled Hereford cows 3 to 12 years old. Bulls ran with the cows. Most cows became pregnant, which lessened observations as the breeding season progressed. Detectors were placed on rumps with adhesive according to directions. Generally, the front edge of the detector was farther to the rear on heavier cattle than on lighter cattle.First observation was May 28, 1968. Observations then were made weekly for 9 weeks, by checking for presence or absence of detectors. All cows that lost detectors or had the detector activated were palpated rectally to determine if ovulation had occurred. If the detector was present and unactivated, it was noted if dye had leaked in the detector.
Keywords: Cattlemen' s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Kamar heatmount detection